Flower-like manganese-cobalt oxysulfide supported on Ni foam as a novel faradaic electrode with commendable performance. (10th February 2016) - Liu, Meitang; Fu, Yu; Ma, Hongwen; Wang, Tianlei; Guan, Chao; Hu, Kunran
Abstract: Flower-like manganese-cobalt (Mn-Co) oxysulfide supported on Ni foam substrate is synthesized by two-step hydrothermal method as binder-free faradaic electrode for charge storage. The crystalline phase and morphology of as-fabricated materials are well-characterized by X-ray diffraction (XRD), Scan electron microscope (SEM), and X-ray photoelectron spectrum (XPS). The results demonstrate that the Mn-Co oxysulfide exists as polycrystal and sulfide are successfully partially substituted into Mn-Co oxide. Impressively, the Mn-Co oxysulfide electrode exhibits excellent electrochemical performance with an ultrahigh specific capacity of 490 C g −1 at 2 A g −1 and 415 C g −1 at 20 A g −1 which is much higher than 301 C g −1 at 2 A g −1 and 174 C g −1 at 20 A g −1 of the Mn-Co oxide nanosheets electrode. Moreover, the flower-like Mn-Co oxysulfide electrode also reveals good cycling stability with 86.5% capacity retention at high current density of 20 A g −1 after 3000 cycles. Because of the flower-like structure and partial substitution by sulfide, which provides large reaction surface area and more flexible structure, Mn-Co oxysufide electrode with excellent electrochemical performances would have great prospect for energy storage device applications.